Towards a circular economy: evaluation of waste management performance in European Union countries - Marković, Milan; Popović, Zoran; Marjanović, Ivana (Serbian Journal of Management, 2023)
Achieving the goals of the circular economy implies taking actions aimed at waste reduction which can be implemented through suitable waste management principles. The idea of the paper is to evaluate and compare the performance of waste management at the level of the European Union (EU). The paper aims to construct a composite index based on selected indicators from the Eurostat database using multi-criteria analysis methods. The CRITIC method was used as a method for determining weight coefficients, while Grey Relational Analysis (GRA) was used as a method for calculating the composite index of waste management performance. The results indicate that the countries of Western and Central Europe record the best results in creating adequate waste management practices (Belgium, the Netherlands, Slovenia, Luxembourg and Austria). It is also noticeable that the countries that joined the EU much later have the lowest values of the index that measures waste management performance, such as Bulgaria, Romania, Cyprus, Slovakia, Croatia, Malta and Poland, respectively. In the coming period, policymakers must pay more attention to respect for the principles of waste management in the newer member states of the EU, in order to reach convergence in the future.